UF/IFAS Standardized Fertilization Recommendations for Agronomic Crops: SS163/SL129, rev. 10/2021 - Mylavarapu, Rao; Wright, David; Kidder, Gerald (EDIS, 2021)
This publication presents in abbreviated form the fertilization recommendations for agronomic crops based on soil tests performed by the UF/IFAS Extension Soil Testing Laboratory (ESTL). It contains the basic information from which ESTL soil-test reports and fertilization recommendations are generated. Correction to Table 1 made 11/29/2021.